On Core Sorting in RMTS and RMTO Systems: A Newsvendor Framework1. (14th September 2015) - Li, Xiang; Li, Yongjian; Cai, Xiaoqiang
ABSTRACT: Variation in core condition and uncertainty in market demand pose great challenges for remanufacturers to match supply with demand. This article investigates a firm that acquires and remanufactures cores of multiple quality conditions to satisfy demand. Both remanufacturing‐to‐stock (RMTS) and remanufacturing‐to‐order (RMTO) systems are considered. In each system, a sorting operation that resolves the core conditions before remanufacturing may or may not be adopted, leading to four possible sorting/remanufacturing strategies: (1) no sorting in RMTS; (2) sorting in RMTS; (3) no sorting in RMTO; and (4) sorting in RMTO. Under each strategy, we derive the optimal decisions on the acquisition and remanufacturing quantities, in two scenarios, respectively: (i) all acquired cores are remanufacturable and (ii) some cores are non‐remanufacturable. We find that sorting can be completely useless to RMTS system, and thus should never be adopted regardless of the sorting cost. We provide the analytical condition under which this ineffectiveness of sorting occurs. Nevertheless, sorting is always useful to RMTO system and should be adopted when the sorting cost is below a threshold value. We also conduct an extensive numerical study and show that the effects of sorting to RMTO system are more significant than that to RMTS system.